Efektivitas Layanan Informasi dengan Metode Ceramah dan Diskusi untuk Mengubah Persepsi Siswa Tentang Disiplin Belajar: Array - Ledita Ezy Maulany; Firman; Netrawati (Citra Dharma Cindekia, 2022)
There are still many students who have wrong perceptions about the discipline of learning that makes them dare to violate the rules or regulations that exist in a school. This happens because students do not know well and completely about the meaning of learning discipline, so more effort is needed to change student perceptions. One of the efforts that is mostly made by school counselors or guidance counseling teachers is to provide information services using the lecture and discussion method in changing students' perceptions of learning discipline.